First Five Years Performance of FDG PET-CT in Institute of Nuclear Medical Physics, SavarAbstract to be submitted Bangladesh J. Nuclear Med. 27(1): page, 2024 (Bangladesh Journal of Nuclear Medicine, 2024)
Background:  In an effort to improve Bangladesh’s molecular imaging capabilities, the Institute of Nuclear Medical Physics (INMP), Savar, which is governed by the Bangladesh Atomic Energy Commission (BAEC), inaugurated its first FDG PET CT scan in September 2018. We will take a look at the first five years of FDG PET CT services provided to cancer patients at INMP in this article. Patients and Methods: The patients were advised to fast overnight before the day of the scan. A whole-body PET-CT scan was acquired with Philips 128-slice Ingenuity TF, one hour after intravenous injection of 18F FDG. Patients who had undergone FDG PET CT scans at INMP, Savar, from September 2018 to December 2023 were retrospectively included, and INMP report databases were reviewed for demographic analyses. Results: A total of 2879 patients underwent FDG PET CT scans for various clinical oncological and non-oncological indications from September 2018 to December 2023. In 2018, a total of 27 patients were scanned in the first year of the inauguration of FDG PET CT at INMP, Savar. Thereafter, 332 in 2019, 469 in 2020, 399 in 2021, 716 in 2022, and 936 in 2023 were scanned subsequently. A total of 12 patients underwent PET-CT scans for non-oncological indications; among them, tuberculosis was 75%. The top five most common primary malignancies were lymphoma (26.4%), carcinoma breast (21%), gastrointestinal carcinoma (9.6%), carcinoma lung (8.8%), and carcinoma ovary (4.6%). Among 762 lymphoma patients, non-Hodgkin’s lymphoma was 58.5%. The majority of patients were more than 61 years of age, with male predominance (52%). The percentage of DM was 34.0%, and dyslipidemia was 27%. Among 980 diabetic cancer patients, 78 had fasting hyperglycemia and required insulin injections before a PET-CT scan. Conclusions: Despite the COVID-19 pandemic and initial uncertainty about FDG availability, there has been a notable increase in FDG PET-CT scanning in INMP from 2018 to 2023. This considerable upsurge is extremely rewarding and plays a critical role in cancer management nationally.Bangladesh J. Nuclear Med. 27(1): 27-33, 2024